(untitled) (Quinto Sol, 2018)
This article is part of a general interest to reconstruct uses and resignifications of the Peronist past by Montoneros and analyzes the role of some of these representations in the construction of their ideas and political options. In the first place, the conditions in which Juan Domingo Perón was overthrown in 1955 and the measures of a material and symbolic nature through which the elimination of the Peronist identity was sought are traced. Second, it reviews the main milestones of the Peronist Resistance, which arose in response to attempts to bury Peronism, and the construction of a myth of popular struggle based on the transmission of memories about those experiences. Third, it systematizes the use of the political formula of the resistance in Montoneros at different central moments in its history, and shows the ambiguous use of that notion, which served both to refer to the Resistance myth and to account for strategies of struggle that were assumed. The article shows an ambiguous use of the term resistance, as a sign of identity, product of a self-perception of Montoneros as an incarnation of a set of struggles initiated in 1955; and as a fighting strategy.